2015
DOI: 10.1039/c5ra11674k
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-induced change of the crystal structure and enhanced stability of the Au11 nanocluster

Abstract: In this paper, we report a highly stable gold nanocluster co-protected by the selenophenol and 1,5bis(diphenylphosphino)pentane (L 5 for short) ligands, formulated as [Au 11 (L 5 ) 4 (SePh) 2 ] + . The structure of this nanocluster is determined by X-ray crystallography. The L 5 -ligands are in the form of "Au-PPh 2 (CH 2 ) 5 Ph 2 P-Au", similar to the "staple motif" in the Au n (SR) m nanoclusters. The purity of this nanocluster is confirmed by electrospray ionization mass spectrometry (ESI-MS) and the thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 60 publications
(57 reference statements)
1
22
0
Order By: Relevance
“…[ 45,63 ] On the other hand, for the same gold core structure, or even different gold cores that share the same gold building units, the UV-Vis spectra always show similar absorption features, regardless of the phosphine ligands. [ 46,64 ] Their UV-Vis-NIR spectra are very similar and show strong absorption peaks at ≈310 and 420 nm, and weak peaks at ≈380 and 515 nm, as documented in [ 50,51 ] which consists of an icosahedral Au 13 building unit with an extra Au 7 clamp as a new layer. It was observed that the [Au 20 (PP 3 ) 4 ]Cl 4 cluster gave similar UV-Vis-NIR spectral features as the previously known icosahedral cluster, [Au 13 (dppe) 5 Cl 2 ]Cl 3 (dppe = 1,2-bis(diphenyl-phosphino)ethane, C 26 H 24 P 2 ) at ≈360 and ≈490 nm.…”
Section: Uv-vis-nir Spectroscopy Of Phosphine-protected Auncsmentioning
confidence: 91%
“…[ 45,63 ] On the other hand, for the same gold core structure, or even different gold cores that share the same gold building units, the UV-Vis spectra always show similar absorption features, regardless of the phosphine ligands. [ 46,64 ] Their UV-Vis-NIR spectra are very similar and show strong absorption peaks at ≈310 and 420 nm, and weak peaks at ≈380 and 515 nm, as documented in [ 50,51 ] which consists of an icosahedral Au 13 building unit with an extra Au 7 clamp as a new layer. It was observed that the [Au 20 (PP 3 ) 4 ]Cl 4 cluster gave similar UV-Vis-NIR spectral features as the previously known icosahedral cluster, [Au 13 (dppe) 5 Cl 2 ]Cl 3 (dppe = 1,2-bis(diphenyl-phosphino)ethane, C 26 H 24 P 2 ) at ≈360 and ≈490 nm.…”
Section: Uv-vis-nir Spectroscopy Of Phosphine-protected Auncsmentioning
confidence: 91%
“…[11][12][13] Ligands play a crucial role in the stabilization of nanoclusters. [14][15][16][17] The non-covalent interactions between surface ligands not only alter properties of clusters but also have signicant effects on nanocluster assembly and selfassembly. [18][19][20][21][22][23][24][25][26][27][28][29][30] For instance, Wu and co-workers demonstrated that C-H/p interactions facilitated the chiral arrangement of ligands, and the assembled ligands presented rotational and parallel patterns on the surface of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 To date, a series of Au 11 (PR 3 ) Cl 3 nanoclusters with adjustable ligands have been extensively studied comparing with other nanoclusters. 15,[36][37][38][39] Therefore, Au 11 (PR 3 )Cl 3 clusters are chosen as models to investigate noncovalent interactions in the crystallization of nanoclusters by surface modication.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, SR ligands have become the most common choice for use with gold clusters . Recently, the synthesis of gold clusters protected by other chalcogenates (selenolate (SeR) or tellurolate (TeR); Figure 1(c)) [41][42][43][44][45][46][47][48][49][50][51], by alkynes [52][53][54], or by two kinds of ligand ( Figure 1(d)) [55][56][57][58][59] has also been reported. In this chapter, we focus on gold clusters protected by chalcogenates (Au n (XR) m ; XR = SR, SeR, or TeR) and describe the synthetic procedures, geometric/electronic structures, and physical and chemical properties of these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the physical and chemical properties of these gold clusters are greatly affected by the type of functional group of the protecting ligand. The ligand exchange [2,10,11,29,30,34,47,48,59]).…”
Section: Introductionmentioning
confidence: 99%